Case Report: Life-saving embolization: a rare case of post-traumatic retroperitoneal hematoma from deep circumflex iliac artery rupture - Xu, Hong-wei; He, Cong (Frontiers in Surgery, 2024)
IntroductionRetroperitoneal hematoma with ongoing hemorrhage is a rare but critical condition following blunt abdominal trauma, requiring urgent evaluation and management. This case details a large retroperitoneal hematoma in the right iliac fossa caused by a rupture of the deep circumflex iliac artery (DCIA), successfully treated with transcatheter arterial embolization.Case descriptionA 66-year-old female presented to our hospital six hours after an electric tricycle accident with dizziness, fatigue, hypotension (80/50 mmHg), and tachycardia (105 beats/min). Laboratory tests revealed a hemoglobin level of 9.2 g/dl and a hematocrit level of 27.5%. Contrast-enhanced CT showed an 18 cm × 10 cm × 5 cm retroperitoneal hematoma in the right iliac fossa with active bleeding. Emergent angiography identified the bleeding source as a branch of the right DCIA. Embolization was performed using a microcoil through a coaxial microcatheter positioned proximal to the bleeding site, successfully stopping the hemorrhage. The patient's condition stabilized, and ultrasound monitoring showed a gradual reduction in hematoma size. The patient was discharged two weeks later.ConclusionThis case highlights a rare but severe instance of retroperitoneal hematoma due to DCIA rupture, effectively managed with transcatheter arterial embolization. The utility of contrast-enhanced CT and angiography in diagnosing active bleeding is emphasized, underscoring the efficacy of transcatheter embolization as a critical intervention in such life-threatening situations.